Relación de la motivación y satisfacción laboral con la calidad del servicio de los trabajadores de la universidad san pedro de chimbote - Portales Pairazamán, Manuela (2009)
The intention of this research work was oriented to determine the existence of relation between the variables “motivation” and “labor satisfaction” with the “quality of the service”, in the appointed workers of the University San Pedro of Chimbote; for which, one identified the levels of these variables. For the determination of the sample the proportional stratified random method was used. For the data collection on the two first variables it was used like instrument the test of motivation and labor satisfaction, made by Claudia García, applied to employees of a hospital Otorrino and Oftalmológica, adapted to this investigation; and for the third variable, an interview guide. In order to realise the analysis the descriptive and inferencial statistic was used. The results indicate that all the layers of the workers of this University are located in the level of “very motivated” and “very satisfied labor”, and as far as the quality of the service, all the layers are in “the regular” level. Also, there is significant positive relation between the variables “motivation” and “quality of the service”, and moderate positive relation between the variables “labor satisfaction” and “quality of the service”.